Meningkatkan Kemampuan Berpikir Kreatif Pada Muatan Matematika Menggunakan Model PENA Pada Siswa Kelas V Sekolah Dasar - Naziah, Wafa; ., Maimunah (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2024)
The problem in this study is the low creative thinking skills of students. This problem is due to the lack of student understanding of the material, learning has not given students creativity, learning takes place in one direction, and learning models that have not varied. The effort to overcome this problem is to use the PENA model. The purpose of this study was to analyze students’ creative thinking skills. This study used a qualitative approach with the type of Classroom Action Research conducted for meetings in class V SDN Sungai Bilu 1 Banjarmasin, totalling 30 students, in semester II of the 2023/2024 school year. The type of data used is qualitative data consisting of observation results of students’ creative thinking skills. The result showed that there was an increase in creative thinking skills at each meeting. The ability to think creatively at meeting 1 to meeting 4 increased from 43% to reach 93% with “Very Good” criteria. Based on the result of the study, it can be concluded that in Mathematics content using the PENA model can improve students’ creative thinking skills.